Potential of berry extracts to control foodborne pathogens. (March 2017) - Das, Quail; Islam, Md Rashedul; Marcone, Massimo F.; Warriner, Keith; Diarra, Moussa S.
Abstract: Globally, foodborne diseases continues to be a serious public health problem. Among the infectious bacteria implicated in these diseases, non-typhoidal Salmonella enterica (NTS) serovars are the major cause of hospitalization and death, followed by Campylobacter, Clostridium perfringens, Escherichia coli O157:H7, and Listeria monocytogenes . In addition, the emergence and spread of antibiotic-resistance strains among these bacteria is becoming a worldwide food safety issue. This rise of resistance led to the restriction of antibiotics use in animal productions in the European Union and application of a possible similar action in the North America. To limit the use of antibiotics in agricultures while satisfying the consumer demands, effective alternative approaches to maintain the animal health and productivity as well as to preserve food need to be explored. In this context, the plant-derived antibacterial compounds could provide novel approaches to control pathogenic bacteria in food industry. In this paper, we review the potential of three different berries (cranberries, blueberries and strawberries) extracts, as alternative antibacterial products against foodborne pathogens. These extracts show various antimicrobial activities against Gram positive ( Listeria, Staphylococcus aureus, and Clostridium perfringens ) and Gram negative ( Salmonella enterica, E. coli and Campylobacter spp.) bacteria. Berry extracts seem to have a pleotropic mode of actions against foodborne bacteria. Several studies on proanthocyanidins from cranberry demonstrated its bactericidal action through anti-adhesion activities and free iron sequestration. Blueberry phenolics were reported to decrease cell auto-aggregation, motility and affect the cellular hydrophobicity. Similar action was observed with strawberry extracts due to their immobilizing capacity. Key research gaps include the effects of processing, bioavailability and detail mechanisms of action of berry compounds. Highlights: In cranberries, A- and B-type proanthocyanidins enhance antiadhesion activities. Hydroxycinnamic acid in blueberries promotes antibacterial activities. In strawberries, ellagic acid shows antibacterial effects. Berry extracts have a pleotropic mode of action against foodborne bacteria. Standardisation of extractions and methodologies of evaluation need to be developed.